A Comparison of the Effectiveness of Online Instructional Strategies Optimized With Smart Interactive Tools Versus Traditional Teaching for Postgraduate Students - Wang, Ping; Ma, Teng; Liu, Li-Bo; Shang, Chao; An, Ping; Xue, Yi-Xue (Frontiers in Psychology, 2021)
To solve the problem that lack of interaction in online courses affects motivation and effectiveness of students’ learning, smart interactive tools were introduced into the online Neurobiology course. This study aimed to evaluate the students’ satisfaction with online teaching mode and assess the academically higher and lower performing students’ learning effectiveness in the online course optimized with smart interactive tools compared to face-to-face learning. Descriptive statistics and independent t-tests were used to describe student samples and determine the differences in students’ satisfaction and performance. Reflections of students’ satisfaction revealed that about 65.8% were satisfied with the learning involvement and about 60.5% were satisfied with the class interaction. Almost two-thirds of the class agreed that the smart interactive tools applied in the online course could help them attain their learning goals better. Among all the smart interactive functions, the class quiz was the most effective one in helping students grasp the main points of the course. No significant differences were found between the two teaching modes in the overall and academically higher or lower performing students’ final exam average scores. Compared to each band score of such two teaching modes, no one failed to pass the final exam in the online course, however, three lower-performing students who were taught in the traditional course failed. This study suggested that optimized online teaching with smart interactive tools could produce the same learning effectiveness for the academically lower-performing students as for the higher-performing students. Meanwhile, the instructors could know the learning status in which each student was and perform personalized guidance and improve exam passing rate accordingly.